Methods for determination of optimal positive end-expiratory pressure: a protocol for a scoping review - Stefan Edginton; Laurent Brochard; Jonathan Gaudet; Helen Lee Robertson; Natalia Kruger; Henry Tom Stelfox; Danny J. Zuege; Kevin J. Solverson; Kirsten M. Fiest; Daniel J. Niven; Sean M. Bagshaw; Ken Kuljit S. Parhar (BMJ Open)
Introduction Titrated application of positive end-expiratory pressure (PEEP) is an important part of any mechanical ventilation strategy. However, the method by which the optimal PEEP is determined and titrated varies widely. Methods for determining optimal PEEP have been assessed using a variety of different study designs and patient populations. We will conduct a scoping review to systematically identify all methods for determining optimal PEEP, and to identify the patient populations, outcomes measured and study designs used for each method. The goal will be to identify gaps in the optimal PEEP literature and identify areas where there may be an opportunity to further systematically synthesise and meta-analyse existing literature.Methods and analysis Using scoping review methodology, we will generate a comprehensive search strategy based on inclusion and exclusion criteria generated using the population, concept, context framework. Five different databases will be searched (MEDLINE, EMBASE, CENTRAL, Web of Science and Scopus). Three investigators will independently screen titles and abstracts, and two investigators will independently complete full-text review and data extraction. Included citations will be categorised in terms of PEEP method, study design, patient population and outcomes measured. The methods for PEEP titration will be described in detail, including strengths and limitations.Ethics and dissemination Given this is a synthesis of existing literature, ethics approval is not required. The results will be disseminated to stakeholders via presentation at local, regional and national levels, as well as publication in a high-impact critical care journal. There is also the potential to impact local clinical care protocols and inform broader clinical practice guidelines undertaken by societies.